Cardiac arrest: An interdisciplinary scoping review of clinical literature from 2020 - Travis W. Murphy; Scott A. Cohen; Charles W. Hwang; K. Leslie Avery; Meenakshi P. Balakrishnan; Ramani Balu; Muhammad Abdul Baker Chowdhury; David B. Crabb; Yasmeen Elmelige; Carolina B. Maciel; Sarah S. Gul; Francis Han; et al. (Journal of the American College of Emergency Physicians Open)
Abstract Objectives The Interdisciplinary Cardiac Arrest Research Review (ICARE) group was formed in 2018 to conduct an annual search of peer‐reviewed literature relevant to cardiac arrest. Now in its third year, the goals of the review are to highlight annual updates in the interdisciplinary world of clinical cardiac arrest research with a focus on clinically relevant and impactful clinical and population‐level studies from 2020. Methods A search of PubMed using keywords related to clinical research in cardiac arrest was conducted. Titles and abstracts were screened for relevance and sorted into 7 categories: Epidemiology & Public Health Initiatives; Prehospital Resuscitation, Technology & Care; In‐Hospital Resuscitation & Post‐Arrest Care; Prognostication & Outcomes; Pediatrics; Interdisciplinary Guidelines & Reviews; and a new section dedicated to the coronavirus disease 2019 (COVID‐19) pandemic. Screened manuscripts underwent standardized scoring of methodological quality and impact on the respective fields by reviewer teams lead by a subject matter expert editor. Articles scoring higher than 99 percentiles by category were selected for full critique. Systematic differences between editors’ and reviewers’ scores were assessed using Wilcoxon signed‐rank test. Results A total of 3594 articles were identified on initial search; of these, 1026 were scored after screening for relevance and deduplication, and 51 underwent full critique. The leading category was Prehospital Resuscitation, Technology & Care representing 35% (18/51) of fully reviewed articles. Four COVID‐19 related articles were included for formal review that was attributed to a relative lack of high‐quality data concerning cardiac arrest and COVID‐19 specifically by the end of the 2020 calendar year. No significant differences between editor and reviewer scoring were found among review articles (P = 0.697). Among original research articles, section editors scored a median 1 point (interquartile range, 0–3; P < 0.01) less than reviewers. Conclusions Several clinically relevant studies have added to the evidence base for the management of cardiac arrest patients including methods for prognostication of neurologic outcome following arrest, airway management strategy, timing of coronary intervention, and methods to improve expeditious performance of key components of resuscitation such as chest compressions in adults and children.